Ideal leader behavior concepts and observed leader behaviors of public elementary school principals in the division of La Union - Rillera, Antonio Bugaoan 1927- (s.n.], 1968)
The study surveyed the chemistry courses required for Biology majors in BSE in several universities in Manila. A detailed discussion of selected chemistry topics and concepts which are directly needed for understanding biological processes is also presented in the study.